1981
DOI: 10.1002/kin.550130912
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the formation of primary products of cumeme cracking over a partially exchanged LaY‐Zeolite

Abstract: The kinetics of formation of primary products from cumene cracking over a partially exchanged LaNaY catalyst have been studied a t 400,450, and 500°C. It has been found that in both the fully and the partially exchanged LaNaY zeolite catalysts the nature of active sites is the same. The higher activity of the fully exchanged catalyst is attributed to a higher concentration of the active sites. It has also been found that an increase in exchange level leads to an increase in the number of both Bronsted and Lewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…Direct evidence for their true nature is not available. Using this nomenclature a detailed mechanism of the primary reactions in cumene cracking has been constructed and is presented in Figure 10 It is interesting to note that studies of this kind have also shown that the activity of HY and LaY is a nonlinear function of the level of exchange [2,18], in agreement with the acidity studies of Ward [19,21] and Sherry [20] who report that strong acidity is a similar nonlinear function of the level of exchange. Figure 3 shows that the rate of the dealky, lation reaction takes off only a~er about 70 or 80 percent of the sodium has been replaced ~" acid-forming cations.…”
Section: (I/t) 3 (K "L)supporting
confidence: 71%
See 1 more Smart Citation
“…Direct evidence for their true nature is not available. Using this nomenclature a detailed mechanism of the primary reactions in cumene cracking has been constructed and is presented in Figure 10 It is interesting to note that studies of this kind have also shown that the activity of HY and LaY is a nonlinear function of the level of exchange [2,18], in agreement with the acidity studies of Ward [19,21] and Sherry [20] who report that strong acidity is a similar nonlinear function of the level of exchange. Figure 3 shows that the rate of the dealky, lation reaction takes off only a~er about 70 or 80 percent of the sodium has been replaced ~" acid-forming cations.…”
Section: (I/t) 3 (K "L)supporting
confidence: 71%
“…Using the procedures described above, initial selectivities in cumene cracking were determined at a variety of temperatures on various catalysts [56][57][58]2]. Table VI shows a set of selectivlties obtained on LaY and HY at three temperatures, together with product-type identification.…”
Section: The Reactions In Ciymene Crackingmentioning
confidence: 99%
“…Besides the main reaction products like benzene, propylene and xylene derivatives, obtained on H(X)-AlMCM-41, some amounts of side reactions products were also detected, such as butene, pentene and traces of butane. Other authors 6,21,22 obtained the same products but with different compositions owing to the catalysts used. Presumably it was due to the different properties of the different products formed inside the catalysts' channels and materials' structures.…”
Section: Reaction Productsmentioning
confidence: 86%
“…A series of experiments in which cumene converted were carried out on ZSM-5 zeolites with a different ionic exchange degree [1][2][3]. Some authors compared the behaviour of some type of zeolites catalysts in cumene conversion and observed distinct differences in the type and the composition of reactions products [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%